Pelatihan Maintenance Diesel Generator Set 3 Phase dan Smart Relay Proteksi di SMKN Sidayu Gresik - Urip Mudjiono; Hendro Agus Widodo; Edy Prasetyo Hidayat; Joessianto Eko Putro (CV. Creative Tugu Pena, 2024)
The aim of this training is Maintenance of Diesel Generator Set 3 Phase and Smart Relay Protection at SMKN Sidayu Gresik. The method used in this training is a combination of quantitative and qualitative methods. A quantitative approach is used to measure the increase in participant competency through pre-test and post-test which will evaluate knowledge and skills before and after training. Participants can properly understand the working principles of generator sets, correct maintenance techniques, and the application of smart relays in protection systems. Through direct practice sessions, participants are able to apply the theory learned in real situations. This shows that the training is not only theoretical, but also very applicable, so that participants are better prepared to face challenges in the field.